2013
DOI: 10.1111/mmi.12238
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of 2‐naphthoyl‐coenzyme A reductase, the prototype of a novel class of dearomatizing reductases

Abstract: SummaryThe enzymatic dearomatization of aromatic ring systems by reduction represents a highly challenging redox reaction in biology and plays a key role in the degradation of aromatic compounds under anoxic conditions. In anaerobic bacteria, most monocyclic aromatic growth substrates are converted to benzoylcoenzyme A (CoA), which is then dearomatized to a conjugated dienoyl-CoA by ATP-dependent or -independent benzoyl-CoA reductases. It was unresolved whether or not related enzymes are involved in the anaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…It is promising that this dehydroxylation could be used to provide aimed anthracycline analogs in the future by protein engineering. In addition, dearomatizations are chemically challenging in a sense both of chemistry and of biology (16,17,27), as the asymmetric hydrogenation of aromatic compounds, which was considered a versatile and practical synthetic strategy method to obtain chiral compound, has been an active and attractive field of methodology research (28,29). Recently, characterization of the NADPH-dependent reductases involved in fungal 1,8-dihydroxynaphthalene melanin, monodictyphenone, and aflatoxin B1 biosynthesis expanded the substrates to hydroxynaphthoquinones and tricyclic anthrahydroquinones (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…It is promising that this dehydroxylation could be used to provide aimed anthracycline analogs in the future by protein engineering. In addition, dearomatizations are chemically challenging in a sense both of chemistry and of biology (16,17,27), as the asymmetric hydrogenation of aromatic compounds, which was considered a versatile and practical synthetic strategy method to obtain chiral compound, has been an active and attractive field of methodology research (28,29). Recently, characterization of the NADPH-dependent reductases involved in fungal 1,8-dihydroxynaphthalene melanin, monodictyphenone, and aflatoxin B1 biosynthesis expanded the substrates to hydroxynaphthoquinones and tricyclic anthrahydroquinones (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, none of these reductions were ATP independent, and, unlike the class I and II benzoyl-CoA reductases, the enzymes were not sensitive to oxygen. Eberlein et al [2013a] purified the 2-naphthoyl-CoA reductase from strain N47 and identified the encoding gene N47_638220, referred to as ncr . The 2-naphthoylCoA reductase is composed of two 73.3-kDa subunits encoded by gene N47_G38220 forming an α 2 -homo dimer of 156 kDa.…”
Section: Aryl-coa Reductases Involved In Anaerobic Naphthalene Degradmentioning
confidence: 99%
“…The protein sequence showed high similarities to members of the flavin-containing 'old yellow enzyme' family, which uses NADPH as cofactor [Sawers, 2015]. Genes within proximity of ncr in the genome are annotated as oxidoreductases, and Eberlein et al [2013a] proposed their function to be electron transfer proteins from a nonidentified electron donor to 2-naphthoyl-CoA reductase. The 2-naphthoyl-CoA reductase assay catalyzed a four-electron reduction to 5,6,7,8-tetrahydro-2-naphthoyl-CoA.…”
Section: Aryl-coa Reductases Involved In Anaerobic Naphthalene Degradmentioning
confidence: 99%
See 1 more Smart Citation
“…the sulfate-reducing Deltaproteobacterium NaphS2 or the enrichment culture N47. During growth of these obligate anaerobes with naphthalene, the 2-naphthoyl-CoA intermediate is first reduced to 5,6,7,8-tetrahydro-2-naphthoyl-CoA (THNCoA) by two flavin-dependent reductases belonging to the old yellow enzyme family [Eberlein et al, 2013a;Estelmann et al, 2015]. These enzymes can be regarded as a third class of dearomatizing aryl-CoA reductases .…”
Section: Distribution/phylogenetic Tree Of Bcrsmentioning
confidence: 99%